Ruling on Theology through the Shari‘a: Modern Approaches of Qur’an Interpretation and the Classical Universal Law of God’s Transcendence - Dhuhri, Saifuddin; Rijal, Syamsul (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2024)
The purpose of this article is to evaluate fatwa on the Wahhabite interpretation of the ambiguous verses in the Qur’an given in 2014. Classical Muslim scholars respected the intellectual freedom of the other theological schools as long as their interpretations did not attribute human characteristics to God. However, this intellectual tolerance is not demonstrated by the Ulama Council in Aceh, Indonesia today, which only accepts their interpretation of the Qur’an. Rival interpretations propagated by other ideological groups, such as the Wahhabites, are ruled as blasphemous and deserve public outcries of condemnation. It seems that the Ulama Council in Aceh has instrumentalized the Shari‘a to suppress any ideas that are not in line with the Ash‘arite creed, even though there are other legitimate schools and approaches. Any group that promotes a different view is now liable to public condemnation.